Clinical manifestations and causes of gelsemium poisoning in Hong Kong from 2005 to 2017: Review of 33 cases. Issue 6 (November 2019) - Chow, Tin Yat Anthony; Ng, Chun Ho Vember; Tse, Man Li
Background: Gelsemium elegans is an extremely toxic plant, but gelsemium poisoning is seldom reported in the English literature. Objectives: To evaluate the clinical manifestations and causes of gelsemium poisoning in Hong Kong. Methods: A retrospective review of gelsemium poisoning recorded by the Hong Kong Poison Information Centre from 2005 to 2017. Results: In total, 33 cases (55% female, median age 44 (interquartile range: 30–56)) were identified in 14 incidences. Consumption of contaminated Ficus hirta (五指毛桃) soup is the commonest cause (52%). Other causes include misidentification of herbs (12%), consumption of parasitic plant Cassytha filiformis (無根藤) (15%) and suicidal ingestion of Gelsemium elegans (斷腸草) (3%). Most patients (94%) had mild to moderate toxicity, with one fatal case and one severe case presented with coma and respiratory depression. All patients complained of dizziness (100%), followed by visual blurring (34%) and nausea (28%). More than half (53%) had ocular manifestations (e.g. visual blurring, ptosis, nystagmus, diplopia) which are not commonly reported in other herbal poisoning. The time of symptom onset was early (median: 50 min (interquartile range: 30–60)) and all occurred within 2 h after oral intake. Most patients (94%) recovered uneventfully with conservative treatment. Conclusion: Most gelsemium poisoning in Hong Kong was due to contamination or misidentification. Early-onset dizziness (<2 h) with ocular symptoms after herbs consumption highly suggests Gelsemium poisoning. Good supportive care, particularly respiratory support, is the mainstay of management. Early recognition and the corresponding preventive measures would be useful.